A Precisely‐Controlled Multichannel Phononic Crystal Resonant Cavity. Issue 12 (10th October 2021) - Zhang, Xiaopeng; Jia, Zhiyuan; Luo, Yangjun; Wang, Yaguang; Liu, Pai; Kang, Zhan
Abstract: Designing multichannel phononic crystal (PnC) resonant cavities working at certain frequencies is highly nontrivial because the defect band location within the band gap must be precisely located. This paper discloses a new methodology of the topological design for the precisely‐controlled PnC resonant cavity. A two‐stage topological design strategy is proposed to determine the frequency ranges of the forbidden and defect bands successively. Complicated topologies of the supercell are represented only with dozens of design variables based on material‐field series expansion model and can be optimized with a gradient‐free optimization algorithm. Different PnC resonant cavity configurations that are difficult to obtain through traditional design methods are realized through the proposed strategy. A multichannel energy harvester is thus designed with the optimized supercell configurations. The device demonstrates a high localization effect (>300%), high frequency resolution of the incident wave (≈0.2 kHz), and a 2 mW power output. Abstract : A new two‐stage topology optimization method for the PnC cavity is proposed, the complicated topologies of the supercell in the PnC cavity are represented only with dozens of design variables based on material‐field series expansion (MFSE) model. Based on the proposed optimization method, a novel multichannel PZT energy‐harvesting device with high frequency resolution is obtained.